Relationship Between Effective Communication About Sexuality in Family And Early Adolescent Attitudes About Free Association Of Students' Vii Grade of Junior High School - Triwibowo, Heri; Heni Frilasari; Puji Lismia Ningrum (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Background: Teenagers need parental guidance to deal with adolescent problems, while during the transitional period, a distance begins to appear between parents and children. And parents still consider it taboo to talk about sexuality with their children. Objectives: The purpose of this study was to determine the relationship between effective communication about sexuality within the family and early adolescent attitudes about promiscuity at Sedati Islamic Middle School, Ngoro District, Mojokerto Regency. Research Methods: Analytical research design with a crossectional approach. The population was 170 students in class VII Islamic Middle School Sedati, Ngoro District, and a sample of 119 students was obtained, which was taken by cluster random sampling. The data was taken using a questionnaire. Results: The results showed that of the 119 respondents who had appropriate effective communication within the family and had a positive attitude, there were 41 students (56.2%), while 35 students (76.1%) had inappropriate effective communication and had a positive attitude. Conclusion: Based on the SPPS test, it shows p (0.001) <alpha (0.05) so H0 is rejected, which means there is a relationship between effective communication about sexuality in the family and early adolescent attitudes about promiscuity at SMP Islam Sedati, Ngoro District, Mojokerto Regency. Effective communication can give appropriate because of openness, perception, media and the environment. However,  the media and environment which are increasingly free, it has an impact on the many negative attitudes that arise even though a lot of effective communication is given appropriately. So it is hoped that parents will be more open to children and monitor children's development.